2020
DOI: 10.1158/1078-0432.ccr-20-0778
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MAN2A1 Enhances the Immune Response to Anti–PD-L1 in Human Tumors

Abstract: Purpose: Immune checkpoint blockade has shown remarkable efficacy, but in only a minority of patients with cancer, suggesting the need to develop additional treatment strategies. Aberrant glycosylation in tumors, resulting from the dysregulated expression of key enzymes in glycan biosynthesis, modulates the immune response. However, the role of glycan biosynthesis enzymes in antitumor immunity is poorly understood. We aimed to study the immunomodulatory effects of these enzymes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 83 publications
0
34
0
Order By: Relevance
“…A recent study found Man2a1-null cancer cells are more sensitive to T cellmediated tumor killing. This finding has translational relevance since pharmacological inhibition of MAN2A1 by swainsonine synergized with anti-PD-L1 in the treatment of melanoma and lung cancer (Shi et al, 2020). In the future, it would be interesting to explore whether circMAN2A1 participates in MAN2A1regulation, and in which manners circMAN2A1 involves in the regulation.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study found Man2a1-null cancer cells are more sensitive to T cellmediated tumor killing. This finding has translational relevance since pharmacological inhibition of MAN2A1 by swainsonine synergized with anti-PD-L1 in the treatment of melanoma and lung cancer (Shi et al, 2020). In the future, it would be interesting to explore whether circMAN2A1 participates in MAN2A1regulation, and in which manners circMAN2A1 involves in the regulation.…”
Section: Discussionmentioning
confidence: 87%
“…It has been well documented that aberrant glycosylation contributes to tumorigenesis in multiple cancer types [18][19][20]. In addition, aberrant glycosylation increased cancer stem cell ability for tumour proliferation [21] and also could weakened immune checkpoint blockade against cancer cells [22,23]. Simultaneously, accumulating data showed that protein glycosylation and trafficking were regulated by the conserved oligomeric Golgi (COG) complex [24].…”
Section: Discussionmentioning
confidence: 99%
“…Later on, Kim et al found that 2-DG, as a PD-L1 deglycosylation agent, synergizes with the epidermal growth factor receptor (EGFR) inhibitor, gefitinib, in syngeneic breast cancer models [ 13 ]. Shi and colleagues integrated previously published clinical studies, functional screens, and omics databases and identified alpha-mannosidase 2 (MAN2A) as a regulator of T-cell dysfunction by controlling N-glycan maturation of PD-L1 in the Golgi apparatus [ 117 ]. Swainsonine, a potent inhibitor of MAN2A1, synergized with PD-L1 blockade in syngeneic cancer models that responded poorly to monotherapy [ 117 ].…”
Section: N-glycosylation As a Target For Cancer Immunotherapymentioning
confidence: 99%
“…Shi and colleagues integrated previously published clinical studies, functional screens, and omics databases and identified alpha-mannosidase 2 (MAN2A) as a regulator of T-cell dysfunction by controlling N-glycan maturation of PD-L1 in the Golgi apparatus [ 117 ]. Swainsonine, a potent inhibitor of MAN2A1, synergized with PD-L1 blockade in syngeneic cancer models that responded poorly to monotherapy [ 117 ]. As described above, B7-H4 depends on N-linked carbohydrates on the extracellular domain to resist proteolysis [ 90 ].…”
Section: N-glycosylation As a Target For Cancer Immunotherapymentioning
confidence: 99%